2016
DOI: 10.1098/rsif.2016.0399
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical modelling of tooth wear

Abstract: Different diets wear teeth in different ways and generate distinguishable wear and microwear patterns that have long been the basis of palaeodiet reconstructions. Little experimental research has been performed to study them together. Here, we show that an artificial mechanical masticator, a chewing machine, occluding real horse teeth in continuous simulated chewing (of 100 000 chewing cycles) is capable of replicating microscopic wear features and gross wear on teeth that resemble wear in specimens collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 46 publications
(86 reference statements)
3
43
0
Order By: Relevance
“…Sharpness index measures the proportion of steeply sloped parts of the surface (Karme, ; Karme, Evans, & Fortelius, ; Ungar et al, ), and it is determined by natural breaks method classification. The natural breaks method divides the surface slopes into three categories, which have as small as possible variation within the groups and as high as possible variance between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…Sharpness index measures the proportion of steeply sloped parts of the surface (Karme, ; Karme, Evans, & Fortelius, ; Ungar et al, ), and it is determined by natural breaks method classification. The natural breaks method divides the surface slopes into three categories, which have as small as possible variation within the groups and as high as possible variance between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…According to experimental studies, grass is the most abrasive food item, consisting of phytoliths and external grit such as silicates from the soil (Karme et al, 2016). Masey O'Neill et al (2010) describe evidence that focal dental overgrowths (modern horses) are more common in those that are stabled and pellet-fed, compared with free-grazing horses.…”
Section: Discussionmentioning
confidence: 99%
“…The height of the focal overgrowth was compared with data provided by Simhofer et al (2008). The rate of wear of the height dimension depends on the diet (Karme et al, 2016), but a rough estimate of the horse's age at the time of death can be developed using the height of a post-canine tooth. We used the wear curve provided by Levine (1982) to estimate the age of KM21814:525 horse at the time of death.…”
Section: Methodsmentioning
confidence: 99%
“…The recent discussion about tooth wear is marked by a debate about the respective contributions of internal plant abrasives (phytoliths) and exogenous abrasives (dust/grit) to the loss of dental tissue (Lucas et al, 2013;Merceron et al, 2016;Rabenold & Pearson, 2014;Sanson, Kerr, & Gross, 2007). Nevertheless, early work suggested that the intake of soil was clearly associated with wear of the incisor teeth in sheep (Healy, 1965); comparative analyses on diet, hypsodonty, and habitat suggest a role of both dietary (internal) and habitat-related (external) abrasives in the evolution of hypsodonty (Kaiser et al, 2013;Williams & Kay, 2001); and both internal and external abrasives are associated with tooth wear in vivo and in vitro (Karme, Rannikko, Kallonen, Clauss, & Fortelius, 2016;Müller et al, 2014). Given these findings and our theory on a reduced effect of external abrasives on the chewing (premolar/molar) teeth in ruminants, the observation of Merceron et al (2016) that dust added to a diet of fresh grass had only little effect on the molar chewing surface appears understandable.…”
Section: Proportion Of Rumination Mastication Classified By Rumiwatch Asmentioning
confidence: 99%